Cohesive devices appearing on Kemal's utterances in Orhan Pamuk's novel The Museum of Innocence - Lestari, Chatarini Septi Ngudi; Wardhono , Agus (Journal of Applied Studies in Language, 2022)
This study is related to the cohesion applied in the novel The Museum of Innocence by Orhan Pamuk. The investigation is focused on the utterances produced by Kemal when talking with Fusun. This paper aims to examine what grammatical and lexical cohesion are used and how these cohesions relate to each other. Because the data were collected in the form of utterances, descriptive qualitative research was applied, and to get a clear understanding of the phenomena that occur in the novel, a content analysis was used. The results showed that Kemal used references, substitutions, ellipsis, and conjunctions in the heading grammatical cohesion and repetition, synonyms, and antonyms in the lexical cohesion heading when talking with Fusun. From these findings, it can be concluded that Kemal’s utterances were constructed through grammatical cohesion and lexical cohesion. Regarding the type of grammatical cohesion, reference is the most dominant, and referring to the type of lexical cohesion, repetition is more often used by Kemal. So it can be said that cohesion analysis plays an important role in creating meaning in communication.